Yielding hydroxyl radicals in the Fenton-like reaction induced by manganese (II) oxidation determines Cd mobilization upon soil aeration in paddy soil systems. (1st January 2022) - Wang, Meng; Liu, Yongbing; Shi, Huading; Li, Shanshan; Chen, Shibao
Abstract: As a redox-sensitive element, manganese (Mn) plays a critical role in Cd mobilization, especially in paddy soil. In an anoxic environment, the precipitation of Mn(II)-hydroxides specifically favors Cd retention, while draining the paddy fields results in substantial remobilization of Cd. However, how the change in Mn redox states during the periodical transit of anoxic to oxic systems affects Cd mobility remains unclear. In this study, we demonstrate that the radical effect generated during the oxidation of Mn(II)-hydroxides exerts a significant effect on the oxidative dissolution of Cd during the aeration of paddy soils. The extractable Cd concentration decreased rapidly during the reduction phases but increased upon oxidation, while Cd availability produced the opposite effect with soil pe + pH and the extractable Mn concentration. Inhibiting the oxidation of Mn(II)-containing phases by microbes suppressed the production of hydroxyl free radicals (OH) and Cd mobilization in the drainage phase. Analysis of X-ray absorption spectroscopy and sequential extraction demonstrated that the transformation from the Mn phase of Mn(II) to Mn(III/IV) determines Cd solubility. Altogether, the oxidization of Mn(II)-hydroxides was associated with the generation of significant amounts of OH. The dissolution of Mn(II)- incorporating phases lead to a net release of Cd into soils during soil aeration. Graphical abstract: Image 1 Highlights: The free radical effect in the Mn-driven Fenton reactions is induced during soil drainage. The radicals promote the oxidative dissolution of Mn(II)-containing phases and Cd release. The transformation of Mn phases (Mn(II) to Mn(III/IV)) determines Cd solubility. Catalytic traits of amorphous Mn oxides in Fenton-like H2 O2 degradation are affirmed.